Consanguinity marriage and fertility outcome health in the middle Euphrates of Iraq - ojs_admin; AL-Rekaby, H. R. Mubarek (University of Thi-Qar Journal of Science, 2019)
The inbreeding coefficient refers to the degree of advancing of any society. In 2006 an experiment was conducted to find the inbreeding coefficient in the middle Euphrates area of Iraq (Al-Qadisiyia and Babylon) and to study the relationship between the related and unrelated marriages as well as reproductive parameters. Results indicated that inbreeding coefficient was (F=0.0167). The percentage of unrelated marriage was higher in ( Al-Qadisiyia 44.9% compared to Babylon 36.5%) and the total was 55.3% Non–fertile families in middle Euphrates region was 2.5% No relationship was found between fertility outcome and consanguineous, non-consanguineous marriage.